Litterfall under Different Aged Chir Pine Stands in Shiwalik Hills of Himachal Pradesh in North-western Himalayas - Sharma, J. K.; Sharma, Sandeep (Indian Forester, 2007)
The litterfall under sapling, pole and mature stands of Chir pine in Shiwalik hills of Himachal Pradesh have been studied. The litter comprised of needles, twig and bark in sapling and pole stands whereas in mature stands, the cones were also included. The litterfall was maximum in summer months i.e. April and May in sapling, pole and mature Chir pine stands but was also influenced by the micro-climatic conditions of that year. The needles had the maximum share (93 to 99%) in total litter under all the Chir pine stands. The average annual litterfall recorded under sapling, pole and mature Chir pine stands was 44.53, 73.72 and 76.39 q/ha, respectively in Shiwalik hills. It was also found that one third needle litter fall occurred in April and May months causing forest fires in Chir pine forests. The information evolved from the present study may be beneficial for devising management strategires for Chir pine needle litter.